PENGUASAAN PENULISAN HIRAGANA YOUON SISWA SMAN 12 PADANG - mayang gita tamara; hendri zalman (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2023)
The background of this research is there are still many student errors in writing hiragana letters, especially youon hiragana and there has been no specific assessment of your hiragana quantitatively at SMAN 12 Padang. The purpose of this study was to describe the writing of hiragana youon in class X SMAN 12 Padang. The type of research used in this research is quantitative method with descriptive data presentation type. The population in this study were students of class X SMA Negeri 12 Padang totaling 108 students. The sample in this study were students of class X SMA N 12 Padang totaling 30 people. The data of this research is the test scores of students' writing mastery of hiragana youon. Based on the results of research that can be carried out, it can be ascertained that your mastery of hiragana is generally in the "adequate" qualification with an average of 56.6.